Analisis Peramalan Jumlah Kunjungan Mahasiswa Prodi XP Ke Perpustakaan Kampus Dengan Metode Least Square - Anzalni, Aulia; Nhajihaq, Nhajihaq; Ananta, Rachel; Rachmasari Pramita Wardhani; Sarungu, Selvia (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2025)
A prediction system for determining the number of student visits is one way to determine the priorities and the number of students interested in literacy culture each year. Creating a prediction system requires a robust calculation method, which is why a prediction system is needed. This prediction system uses the Least Squares method. Based on the research conducted, the system can implement the Least Squares method to predict students studying and using library facilities. This helps library administrators prepare the necessary needs for students who wish to study in the library.